REMOTE BANKING MAINTENANCE AS THE MEANS OF BANKING SERVICES MODERNIZATION - P. Burmistrova; E. Shatalova (Вестник университета)
The article considers the main features of remote banking services as a means of improving the activities of banking institutions and gaining competitive advantages at the current stage of development of the national banking system. The main types of remote banking maintenance have highlighted. The main types of risks, associated with servicing in the remote mode for both banks and their clients have identified. The factors that hamper the development of remote service in Russia and the potential ways to overcome them have determined.